Acute effects of BFR intra-conditioning on torque and muscle activity of the rectus femoris muscle during isokinetic knee extensions - Krzysztof Fostiak; Marta Bichwoska-Paweska; Robert Trybulski; Dan Iulian Alexe; Michal Wilk (Scientific Reports)
Abstract The study aimed to evaluate the impact of blood flow restriction (BFR) used only before sets of isokinetic knee extensions on torque and muscle activity of the Rectus Femoris muscle. Twenty healthy physically active males (age = 22.7 ± 6.7 years; body mass = 83.0 ± 15.9 kg; body height = 180.8 ± 8.3 cm) performed three experimental sessions in a random crossover design (BFR - with blood flow restriction; control - without BFR, Sham). In the BFR and Sham conditions cuffs were applied for 5 min and released 1 min prior to each set of isokinetic knee extensions. The pressure of the cuffs was 80% AOP (arterial occlusion pressure) for BFR conditions and 20 mmHg for Sham conditions. For Control conditions no restriction was applied. Experimental sessions consisted of 5 sets of 3 isokinetic knee extensions (180°/s) with 6.5-min rest intervals between sets. The repetitions were performed with maximal effort. During the concentric phase of the exercise peak torques and peak electromyographic activity of Rectus Femoris muscle were gathered. The eccentric phase was passive. The two-way repeated measures ANOVA did not show statistically significant condition × set interaction for peak torque and muscle activity. There was also no main effect of condition as well as no main effect of set for peak torque and muscle activity. The results of this study indicate that BFR intra-conditioning (5 min; 80% AOP; 1 min reperfusion) did not significantly affect strength performance or Rectus Femoris EMG activity. However, the lack of performance decline suggests it does not impair neuromuscular output, which may be beneficial in high-load training with long rest intervals. Previous research shows that BFR may induce adaptive changes not examined here. Further studies should explore these adaptations and the effects of varying BFR parameters, intensities, and work to rest ratios.